Euforia Pemilu Legislatif, Pilpres Dan Pemilukada Serentak Di Indonesia - Orien Effendi (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2021)
Euphoria of the Legislative Election, Presidential Election and Regional Head Election Simultaneously in Indonesia. Since the collapse of the New Order government in 1998, the enthusiasm of the Indonesian people in welcoming the atmosphere of the birth of the first democratic system by holding direct elections has been great. Through direct elections at that time began the election of the president and vice president elected by the people for the first time. The direct election by the people also applies to elections at the regional level which include the election of regional heads. Meanwhile, in the course of history, legislative elections have been held long before starting in 1955, so that it is recorded that legislative elections have been held 12 (twelve) times since they were held for the first time until their implementation in 2019. Along the way, the legislative, presidential and post-conflict local elections showed high enthusiasm in facing various challenges in each election period. So that the Indonesian people continue to learn from history and improve all deficiencies which then produce maturity in democracy. By reviewing the literature, this paper tries to review events related to the spirit or euphoria of the election.